(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
Court proceedings in the field of medical law are currently a growing issue given the increasing migration of doctors and medical staff. Because of that fact, it is crucial to establish the standard of quality of health protection in the European Union (EU). Following the presentation of the existing levels of protection connected with the prevention of malpractice, the paper distinguishes between the legal documents of the EU and the Council of Europe because many documents related to health care and quality are adopted in the EU and in the Council of Europe. The general conclusion is that there is no uniform or cross-sectoral definition of quality in health care, however it has been found that important elements of health care quality include effectiveness, efficiency, access, safety, equity, appropriateness, timeliness, acceptability, satisfaction, patient responsiveness or patient-centeredness, and continuity of care. The health care aspect is analysed in the continental legal system and the common law legal system. The issue of causation is observed through different theories in the continental legal system and various case law examples in the common law legal system. The authors concluded that it would be preferable to adopt a theory of objective imputation as a legal standard for causation in criminal liability in medicine, because it analyses several possible causes in close or remote connection with the resulting consequence, i.e. said theory considers as relevant only the legal causes that result in a harmful event through the violation of due diligence. The paper primarily deals with criminal liability for malpractice, but it also presents the civil aspects in the states (for example the USA) which recognise only civil liability for malpractice.